Developing guided inquiry-based ecosystem module to improve students’ critical thinking skills - Irwan Irwan; Maridi Maridi; Sri Dwiastuti (University of Muhammadiyah Malang, 2019)
The availability of modules that are able to develop critical students' thinking skills has not been fulfilled. This study aimed to develop and determine the characteristics, feasibility, and effectiveness of guided inquiry-based ecosystem modules to improve students' critical thinking skills. This R&D research referred to Borg and Gall model with nine stages. The research instrument used was a test question sheet adapted from Facione. The data gained were analyzed using ANCOVA. The results of the study showed that: 1) the developed module was characterized with guided inquiry-based syntax and critical thinking skills aspect; 2) the module was declared feasible based on the gained validity scores i.e. 92.19 (very decent) from material expert, 81.90 (very decent) from learning expert, 78.57 (worthy) from linguist, 92.86 (very decent) from learning media expert, 92.36 (very decent) from practitioners, and 91.80 (very decent) from limited field test; 3) the student critical thinking skills achievement which treated by using the module was significantly higher compared to another class (F = 120.52; p-value < 0.05). It can be concluded that the developed module was feasible to be used in learning and effectively improved students' critical thinking skills.